Dairy Fermentation 2.0 - Thomas Bintsis (Fermentation)
The manufacture of fermented dairy products has a long history, and such products are produced globally, following artisanal or industrial fermentation processes, satisfying consumers’ need for healthy, nutritious, delicious and safe foods [...]